(untitled) (International Seven Journal of Multidisciplinary, 2025)
Umbilical hernia is a common condition in ruminants, particularly in calves and other young animals, characterized by the protrusion of abdominal organs through an opening in the umbilical ring. This article aims to review the surgical procedures used to correct umbilical hernias in domestic and wild ruminants, comparing the most effective treatment strategies. The methodology adopted was a review of the scientific literature, with analysis of articles on diagnosis, conservative and surgical treatment, and postoperative care. The results indicate that while small hernias can be treated conservatively with bandages, larger ones require surgical intervention, with herniorrhaphy using polypropylene mesh being the most effective technique to prevent recurrence. In wild ruminants, such as camels, the approaches are similar, but adapted to the anatomical particularities of these species. The research concludes that the surgical technique, combined with early diagnosis and adequate postoperative care, results in good recovery rates in both domestic ruminants and wild ruminants in captivity.